2020
DOI: 10.3390/ma13010226
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Concrete Containing Recycled Glass Aggregates Produced of Exploded Lighting Materials

Abstract: The paper presents an analysis of the possibilities of using glass waste from recycled lighting materials as aggregates for cement concrete. The research material was obtained from a company that utilizes electrical waste. Glass from pre-sorted elements was transported to the laboratory and crushed in a drum crusher. In this way, the aggregate obtained was subjected to the basic tests that are carried out for aggregates traditionally used in construction. The specific density of aggregate, bulk density, absorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Replacement of natural aggregate with glass aggregate results in a significant increase in concrete strength [ 12 , 13 ], but not in all cases. In contrast, the test results [ 14 ] showed that the greater the addition of recycled glass aggregates produced of exploded lighting materials, the less advantageous the features of the concrete obtained with its participation are. The addition of waste glass as a partial substitute to fine aggregate has been reported to improve the mechanical properties of heat resistant cementitious mortars [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Replacement of natural aggregate with glass aggregate results in a significant increase in concrete strength [ 12 , 13 ], but not in all cases. In contrast, the test results [ 14 ] showed that the greater the addition of recycled glass aggregates produced of exploded lighting materials, the less advantageous the features of the concrete obtained with its participation are. The addition of waste glass as a partial substitute to fine aggregate has been reported to improve the mechanical properties of heat resistant cementitious mortars [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the zone of adhesive-aggregate were also observed in studies [ 5 , 68 ]. However, in publication [ 13 ] certain differences have been observed in density, caused by the growing contents of air in the mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Materials 2020, 13, x FOR PEER REVIEW 3 of 24 [54][55][56][57] and ceramic waste [58,59]. From the ecological and economic viewpoint this solution appears to be advantageous, proecological and safe for the environment.…”
Section: Waste Glass Culletmentioning
confidence: 99%
See 1 more Smart Citation
“…The split tensile strength value decreases with increase in replacement proportions [4]. If the source of glass waste is lighting material the microscopic analysis showed the flat shape causing the accumulation of air beneath the grains in the concrete mix (Drzymała, Zegardło, and Tofilo 2020). In case of CRT glass the densities increases because of low water absorption (Song et al 2019).…”
Section: Discussion On Previous Findingsmentioning
confidence: 99%